Cerebrospinal fluid extracellular vesicle enrichment for protein biomarker discovery in neurological disease; multiple sclerosis. Issue 1 (1st December 2017) - Welton, Joanne L.; Loveless, Samantha; Stone, Timothy; von Ruhland, Chris; Robertson, Neil P.; Clayton, Aled
ABSTRACT: The discovery of disease biomarkers, along with the use of "liquid biopsies" as a minimally invasive source of biomarkers, continues to be of great interest. In inflammatory diseases of the central nervous system (CNS), cerebrospinal fluid (CSF) is the most obvious biofluid source. Extracellular vesicles (EVs) are also present in CSF and are thought to be potential "biomarker treasure chests". However, isolating these CSF‐derived EVs remains challenging. This small‐scale pilot study developed and tested a protocol to enrich for CSF‐EVs, both in relapsing remitting multiple sclerosis (RRMS) CSF and controls. These were subsequently compared, using an aptamer based proteomics array, SOMAscan™. EVs were enriched from RRMS patient ( n = 4) and non‐demyelinating control (idiopathic intracranial hypertension (IIH) ( n = 3)) CSF using precipitation and mini size‐exclusion chromatography (SEC). EV‐enriched fractions were selected using pre‐defined EV characteristics, including increased levels of tetraspanins. EVs and paired CSF were analysed by SOMAscan™, providing relative abundance data for 1128 proteins. CSF‐EVs were characterised, revealing exosome‐like features: rich in tetraspanins CD9 and CD81, size 100 nm, and exosome‐like morphology by TEM. Sufficient quantities of, SOMAscan™ compatible, EV material was obtained from 5 ml CSF for proteomics analysis. Overall, 348 and 580 proteins were identified in CSF‐EVs and CSF, respectively, of which 50 were found to be significantly ( t ‐test) and exclusively enriched in RRMS CSF‐EVs. Selected proteins, Plasma kallikrein and Apolipoprotein‐E4, were further validated by western blot and appeared increased in CSF‐EVs compared to CSF. Functional enrichment analysis of the 50 enriched proteins revealed strong associations with biological processes relating to MS pathology and also extracellular regions, consistent with EV enrichment. This pilot study demonstrates practicality for EV enrichment in CSF derived from patients with MS and controls, allowing detailed analysis of protein profiles that may offer opportunities to identify novel biomarkers and therapeutic approaches in CNS inflammatory diseases.